Transcript dynamics of proinflammatory genes revealed by sequence analysis of subcellular RNA fractions - Bhatt, Dev M; Pandya-Jones, Amy; Tong, Ann-Jay; Barozzi, Iros; Lissner, Michelle M; Natoli, Gioacchino; Black, Douglas L; Smale, Stephen T (Cell, 2012)
Macrophages respond to inflammatory stimuli by modulating the expression of hundreds of genes in a defined temporal cascade, with diverse transcriptional and posttranscriptional mechanisms contributing to the regulatory network. We examined proinflammatory gene regulation in activated macrophages by performing RNA-seq with fractionated chromatin-associated, nucleoplasmic, and cytoplasmic transcripts. This methodological approach allowed us to separate the synthesis of nascent transcripts from transcript processing and the accumulation of mature mRNAs. In addition to documenting the subcellular locations of coding and noncoding transcripts, the results provide a high-resolution view of the relationship between defined promoter and chromatin properties and the temporal regulation of diverse classes of coexpressed genes. The data also reveal a striking accumulation of full-length yet incompletely spliced transcripts in the chromatin fraction, suggesting that splicing often occurs after transcription has been completed, with transcripts retained on the chromatin until fully spliced.